A new Gonatocerus (Hymenoptera: Mymaridae) from Argentina, with taxonomic notes and molecular data on the G. tuberculifemur species complex - Triapitsyn, Serguei V. (2008)
Gonatocerus deleoni Triapitsyn, Logarzo & Virla sp. n., reared from sentinel eggs of Tapajosa rubromarginata (Signoret) (Cicadellidae: Cicadellinae: Proconiini) on citrus plants, a new member of the ater species group of Gonatocerus Nees (Mymaridae), is described from the state of Mendoza, Argentina. Taxonomic notes and host association data are provided to help differentiate this new species from the morphologically similar but genetically distinct taxon, G. tuberculifemur (Ogloblin). The female of the latter is redescribed and the male is newly described. Gonatocerus deleoni, G. tuberculifemur, and three forms (different molecular clades) comprise the G. tuberculifemur complex. These forms are identified but not formally described because of lack of morphologically distinguishing features. The taxonomic conclusions are supported by molecular data, and by results of reciprocal cross-breeding experiments between most of them.